The Psychosocial Impact Of Dental Aesthetics On Orthodontics Patients - Azrul Hafiz Abdul Aziz; Diana Md Zahid; Zurairah Ibrahim; Ainuddin Yushar; Syiral Mastura; Fitri Octavianti; A. Noor Sam (Ectodermal Dysplasia Group-Turkey, 2024)
J Int Dent Me d Res 201 9 ; 12 ( 2 ) : 563568 )